The immunological landscape of traumatic brain injury: insights from pathophysiology to experimental models - Abikenari, Matthew; Ha, Joseph H.; Liu, Justin; Ren, Alexander; Cho, Kwang Bog; Lim, Jaejoon; Kim, Lily H.; Medikonda, Ravi; Choi, John; Lim, Michael (Frontiers in Neurology, 2025)
Traumatic brain injury (TBI) is a complex, heterogeneous neuropathological disease that continues to be among the prominent causes of mortality and disability around the world. Translational success in TBI has been significant, yet therapies are limited as the intersection of the initial mechanical traumas and secondary neuroinflammatory cascades, which predispose to long-term neurological deficits, is poorly understood. The pathogenesis of TBI is not limited to the primary mechanical injury. The secondary damage, including ischemia, excitotoxicity, oxidative stress, and immune dysfunction, leads to neuronal apoptosis, the breakdown of the blood–brain barrier (BBB), and chronic neuroinflammation. The preclinical controlled cortical impact (CCI) and fluid percussion injury (FPI) TBI models have generated valuable biomechanical data related to TBI-induced immune responses, including microglial priming, astrocyte dysregulation, and peripheral leukocyte recruitment. However, experimental models today are unable to completely replicate the intricate immune cascades in human TBI, particularly delayed and context-specific innate and adaptive immune response activation. Cytokine signaling (IL-1β, TNF-α, and IL-6), neuroinflammatory amplification through the IL-23/IL-17 pathway, and autoantibody-mediated neurodegeneration are emerging as significant secondary injury mechanisms. Additionally, TBI-induced immunosuppression, which presents as generalized T lymphocyte depletion and aberrant macrophage polarization, enhances the risk of infection and delayed neurological recovery. Emerging immunotherapeutics such as cytokine blockade, complement blockade, and targeted modulation of T lymphocytes have the potential to optimize the post-TBI immune microenvironment for reducing secondary damage. Inclusion of next-generation experimental models combined with secondary injuries, such as hypoxia, polytrauma, and systemic inflammation, is needed to shift towards innovative, biomarker-driven, patient-stratified trials. Thus, integration of immunological phenotyping with translationally relevant models of TBI represents an important cornerstone in the development of targeted therapeutic treatments designed to improve neuroprotection, repair, and long-term functional outcome.